Utilization of Moss as a Natural Bioindicator for Air Pollution Assessment - Satria Alsahaza; Rizky Hanif Firdaus; M Fikri Mauludan; Syafiq rabbani; Raihan Fataruba; Agung Taufik (GLOBAL SCIENTS PUBLISHER, 2026)
Air pollution is an increasing environmental problem caused by industrial activities, transportation, and human daily activities. One alternative approach to monitoring air quality is the use of bioindicators, which are living organisms capable of reflecting environmental conditions. Mosses have strong potential as air bioindicators because they lack true roots and absorb nutrients directly from the atmosphere, allowing pollutants to accumulate in their tissues. This study aimed to examine the ability of mosses to accumulate air pollutants and to compare air pollution levels across different environments. A descriptive-experimental method was applied by collecting moss samples from industrial areas, high-traffic zones, residential areas, and green spaces. The results showed that pollutant accumulation in moss tissues was higher in industrial and high-traffic areas compared to residential and green areas. These findings indicate that mosses can be utilized as simple, economical, and effective natural bioindicators for air quality monitoring.